MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN MELALUI MEDIA SEQUENCING PICTURES BAGI ANAK KESULITAN BELAJAR MEMBACA - Mia Hermiati (Universitas Negeri Padang, 2014)
Abstrack: This research was conducted due to the problem found at SD N 17 Jawa Gadut, Padang indicating that a student with reading disabilities in the fourth grade got problems to read especially in reading comprehension. The student’s ability was very low and he could not answer questions related to the text being read. Based on this problem, the current research was designed for revealing whether the use of sequencing pictures could improve reading comprehension of the student with reading disabilities in the fourth grade of SD N 17 Jawa Gadut, Padang. This was an experimental research which used Single Subject Design (SSD) and A-B design. The data gotten was analyzed by using graphic visual anlaysis. The subject of the research was the student with reading disabilities. Based on the result of the research it was conclude that the use of sequencing pictures could improve reading comprehension ability of the student with reading disabilities in the fourth grade of SD N 17 Jawa Gadut, Padang. The researcher suggests the teacher to make use of sequencing pictures to teach Indonesian Language especially in reading comprehension. Kata kunci: Media Sequencing Pictures; Kemampuan Membaca Pemahaman.